PENGEMBANGAN MEDIA BIG BOOK TERHADAP KEMAMPUAN LITERASI SISWA SEKOLAH DASAR - Hayati, Risaini Huli; Marhamah, Marhamah; Kuswidyanarko, Arief (Universitas Negeri Medan, 2024)
This research aims to produce big book learning media for students' literacy skills in the material of recognizing the syllables